Epidural Corticosteroid Injections for Sciatica - Oliveira, Crystian B. [UNESP]; Maher, Christopher G.; Ferreira, Manuela L.; Hancock, Mark J.; Oliveira, Vinicius Cunha; McLachlan, Andrew J.; Koes, Bart W.; Ferreira, Paulo H.; Cohen, Steven P.; Pinto, Rafael Z. (Lippincott Williams & Wilkins, 2020)
Study Design. Systematic with meta-analysis Objectives. The aim of this study was to investigate the efficacy and safety of epidural corticosteroid injections compared with placebo injection in reducing leg pain and disability in patients with sciatica. Summary of Background Data. Conservative treatments, including pharmacological and nonpharmacological treatments, are typically the first treatment options for sciatica but the evidence to support their use is limited. The overall quality of evidence found by previous systematic reviews varies between moderate and high, which suggests that future trials may change the conclusions. New placebo-controlled randomized trials have been published recently which highlights the importance of an updated systematic review. Methods. The searches were performed without language restrictions in the following databases from 2012 to 25 September 2019: Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, MEDLINE In-Process & Other Non-Indexed Citations, PubMed, Embase, CINAHL, PsycINFO, International Pharmaceutical Abstracts, and trial registers. We included placebo-controlled randomized trials investigating epidural corticosteroid injections in patients with sciatica. The primary outcomes were leg pain intensity and disability. The secondary outcomes were adverse events, overall pain, and back pain intensity. We grouped similar trials according to outcome measures and their respective follow-up time points. Short-term follow-up (>2 weeks but <= 3 months) was considered the primary follow-up time point due to the expected mechanism of action of epidural corticosteroid injection. Weighted mean differences (MDs) and risk ratios (RRs) with their respective 95% confidence intervals (CIs) were estimated. We assessed the overall quality of evidence using the GRADE approach and conducted the analyses using random effects. Results. We included 25 clinical trials (from 29 publications) providing data for a total of 2470 participants with sciatica, an increase of six trials when compared to the previous review. Epidural corticosteroid injections were probably more effective than placebo in reducing short-term leg pain (MD -4.93, 95% CI -8.77 to -1.09 on a 0-100 scale), short-term disability (MD -4.18, 95% CI: -6.04 to -2.17 on a 0-100 scale) and may be slightly more effective in reducing short-term overall pain (MD -9.35, 95% CI -14.05 to -4.65 on a 0-100 scale). There were mostly minor adverse events (i.e., without hospitalization) after epidural corticosteroid injections and placebo injections without difference between groups (RR 1.14, 95% CI: 0.91-1.42). The quality of evidence was at best moderate mostly due to problems with trial design and inconsistency. Conclusion. A review of 25 placebo-controlled trials provides moderate-quality evidence that epidural corticosteroid injections are effective, although the effects are small and short-term. There is uncertainty on safety due to very low-quality evidence.
Keywords: adrenal cortex hormones; epidural; injections; placebos; sciatica